Quadruple Helix Model on Creative Economy Development in Bandung Regency - Hadiyanto, Ferry; Kharisma, Bayu; Remi, Sutyastie S.; Apriliadi, Ardi (International Journal of Criminology and Sociology, 2022)
This paper uses the quadruple helix model and creative economy as research variables. This study is conducted on the creative sector in Bandung Regency. The research process is mainly executed through focus group discussion (FGD) with all essential parties and interviews with stakeholders in regional work units. The FGD and interview procedure will generate accountable information related to (1) Potential map for the creative economy; (2) SWOT analysis and available partnership programs for the development of the creative economy; (3) a description of cooperation system between related parties in Quadruple helix; (4) Conception of a government partnership program with creative communities through program activities. This study's significant result indicates that the role of government in Quadruple helix cooperation is 60 percent in 2016 and decreasing to 10 percent in 2019. The reduction of the governmental function is also accompanied by the increasingly dominant role of creative entrepreneurs each year, reaching 55 percent in 2019. This phenomenon shows that the development of the creative economy is becoming more independent every year.